Unpacking the Landscape of Digital Ecosystem Readiness: A Decade of Insights Through Bibliometric Analysis: A Decade of Insights Through Bibliometric Analysis - Prihatini Ade Mayvita; Kumara Efrianty; Ervica Jamilah; Ana Sofia Herawati; Gusti Meinar Girda Ariani; Nurul Hasanah (Cita konsultindo, 2025)
Recently, the urgency of preparing digital ecosystems for rapid change has attracted growing scholarly attention. This study explores how research on Digital Ecosystem Readiness (DER) has developed over the past five years, focusing not only on organizational preparedness but also on broader system-wide dynamics. While earlier studies mostly looked at small-scale details, this paper seeks to identify new trends, themes, and missing areas by reviewing 57 articles published between 2021 and 2025, taken from Scopus and Google Scholar. Using PRISMA guidelines to choose articles, the data were examined with VOSviewer, which created various visual tools like co-occurrence networks and maps showing how authors work together. Key findings show a shift from internal technological adoption toward topics like platform governance, AI integration, and policy-based digital sustainability. Despite growing interest, research on ecosystem-level readiness appears fragmented, with limited cross-national academic collaboration. The study suggests that current models could improve by using a broader approach that includes Technology–Organization–Environment theory, dynamic capability perspectives, and multi-stakeholder governance methods. This integrative view is essential for designing inclusive readiness strategies that reflect the realities of a fast-evolving digital world.